2022
DOI: 10.3389/fpsyg.2022.764811
|View full text |Cite
|
Sign up to set email alerts
|

Building the Positive Emotion-Resilience-Coping Efficacy Model for COVID-19 Pandemic

Abstract: The world faces unprecedented challenges because of the Coronavirus Disease 2019 (COVID-19). Existing theories of human flourishing and coping efficacy are too broad and general to address COVID-19 unprecedented mental health challenges. This study examined two main objectives, first the associations between psychological outcomes (i.e., depression, anxiety, and stress) and psychological wellbeing of this phenomenon, and second, moderating and mediating factors emotions, resilience and coping self-efficacy. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 77 publications
(80 reference statements)
2
21
0
Order By: Relevance
“…Second, mental health practitioners are encouraged to apply a purposeful designed "Positive Emotion-Resilience-Self Efficacy (PERCE) Model" in their professional practices as a postpandemic recovery approach (9). Research on positive emotion evidenced the association to improve reactions to aversive stimuli and promote resilience (83).…”
Section: Implications For Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Second, mental health practitioners are encouraged to apply a purposeful designed "Positive Emotion-Resilience-Self Efficacy (PERCE) Model" in their professional practices as a postpandemic recovery approach (9). Research on positive emotion evidenced the association to improve reactions to aversive stimuli and promote resilience (83).…”
Section: Implications For Practicementioning
confidence: 99%
“…In Malaysia, the unemployment rate had shot up from 3.9 to 5% in April 2020, peaking at 5.3% in May 2020 (7). Among retrenched Malaysians, a large proportion reported experiencing severe depression, anxiety, and stress (8,9). Recent reports have predicted deterioration in mental health as a secondary crisis following health worries and economic fallout of the COVID-19 pandemic (10).…”
Section: Introductionmentioning
confidence: 99%
“…How stressors were perceived and which effects these may have on subjective wellbeing can differ, depending on the individual situation, personality, and coping strategies of the affected people. Coping self-efficacy and resilience as resources were identified to mediate the effect of psychological stressors such depression, anxiety, and stress on psychological wellbeing ( 17 ) and thus should be integrated in pandemic-related recovery strategies. Resilience as an ability to adapt to adverse situations is a factor that relates to how one is able to cope with stress and its negative effects ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Psychological resilience, which refers to an individual's ability to cope with various challenges and to flexibly overcome external pressures, may develop with personal growth and change (Ai and Hu, 2016 ). Resilience has become widely studied in psychology as an individual coping resource to resist external pressure (Ke et al, 2022 ). A study on Arab youth found that the COVID-19 worry negatively predicts psychological resilience and brings them more mental health disorders (Yildirim et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%